FAKTOR-FAKTOR YANG MEMENGARUHI PERSEPSI WAJIB PAJAK MENGENAI ETIKA ATAS PENGGELAPAN PAJAK (TAX EVASION) - Dewi, Trie Julianti; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2017)
Tax is the most important element in supporting the budget revenues. The assumption that tax is a burden causes the taxpayer always try to minimize the tax debt and susceptible to fraud such as tax evasion. Many cases of tax evasion in Indonesia indirectly form perceptions of tax payer about  tax evasion behaviour. The purpose of this study is to determine the effect of tax fairness, tax system, discrimination, taxpayer knowledge, and the intensity of tax audits in KPP Pratama Denpasar Timur about tax evasion. Sampling techniques in this study using purposive sampling method. The respondents are 100 individual taxpayer and uses multiple linear analysis techniques. The study results indicate that tax fairness, tax system, taxpayer knowledge, and intensity of tax audits has negative effect on the perception of taxpayer about ethics on tax evasion, while discrimination has positive effect on the perception of taxpayer about ethics on tax evasion.
Keywords: tax fairness, tax system, discrimination, tax payer knowledge, intensity of tax audit